Film dan Mode Ekspresi Keagamaan Masyarakat Muslim Urban - Munirul Hakim, Ahmad (UIN Sulthan Thaha Saifuddin Jambi, 2023)
This research aims to explore the evolution of modes of religious expression in films and understand how urban Muslim communities are represented through religious modes in cinematic works. This research involves the analysis of film as a form of cultural and religious representation, particularly in Muslim urban environments. Through an examination of films representing various time periods, this research will trace the development of religious fashion in Muslim urban contexts. Several approaches are found in looking at the modes of religious expression of Muslim communities in films, namely traditional, contemporary, critical and inclusive modes. It is hoped that the results of this research will provide a deeper understanding of the role of film as a medium for religious expression and how the evolution of religious fashion reflects the dynamics of urban Muslim society. In addition, analysis using four different approaches is expected to provide comprehensive and contextual insight into the complexity of religious expression in urban cinematic contexts.